Direct Copper-Catalyzed C-3 Arylation of Diphenylphosphine Oxide Indoles - Huang, Xiao-Ling; Li, Chong; Wang, Juan; Yang, Shang-Dong (Synthesis, 2021)
We have developed a simple and effective method for the C-3 arylation of phosphorus-containing indole compounds in the presence of CuI under mild conditions. This reaction provides a reliable method for the modification of ligands.
Keywords: transition-metal catalysis; organophosphorus compounds; arylation; indoles